O palácio de papel : cem anos do Arquivo Público do Estado do Rio Grande do Sul (1906-2006) - Merlo, Carmen Moreira (2010)
It is a commemorative occasion, the 100th anniversary of the Rio Grande do Sul Public Archive, in 2006, more than watching its growing, it is the moment to value its past, strengthening its relationship with the users as well as the porto-alegrense society and, mainly, strengthening its image as a traditional cultural institution in the capital city. This paper presents the history of the Rio Grande do Sul Public Archive, since its foundation until the year 2006. In order to understand the Public Archive history it was necessary to follow its acting as a public institution, the Rio-grandense Republic proposal of development and progress,inspired by the early 20th century positivist ideals. Aiming to provide the public administration with an exclusive bureau to keep and preserve the province documents related to the Rio Grande do Sul public administration, history and geography, the President of the Province, Borges de Medeiros, organized a Provincial Public Archive, expressing the 19th century preservationist philosophy. Corresponding to a necessity, the institution of the Public Archive was well conceived by the public opinion , especially by the republican. The opening of the Public Archive was marked by a series of transformations and by the adoption of measures which translated the objectives of the state political power. Therefore,this study deals with the historical origin of the archives from six thousand years ago up to this day, in order to analyze them. This succinct evolution line of the world archives takes us to the appearance of the State archives in Brazil, and specifically in Rio Grande do Sul. The public archives express the trajectory of their public administrations, as well as their political and social conditions. In search for the creation sense of the Rio Grande do Sul Public Archive and its functionality,it was possible to realize the importance the initiative had for the State in the construction of the rio-grandense republicanism. The strategy of building a place to keep the State documentation in its own building represented three aspects: security, preservation (climatization) and centralization, besides its architectural style which is unique in Latin America, maybe unique in the world